Pengaruh Media Sosial terhadap Efektivitas Kampanye Sosialisasi Kesehatan di Era Digital - Siti Silatur Rahmi; Fenny Rahayu Muchlis (Dialogika : Jurnal Penelitian Komunikasi dan Sosialisasi, 2025)
Social media has become an important tool in disseminating health information to the public. This study aims to analyze the influence of social media on the effectiveness of health socialization campaigns in Indonesia. Using survey methods and in-depth interviews, the results of the study indicate that platforms such as Instagram and TikTok are more effective in reaching the younger generation than traditional media. Interactivity and visualization factors of content play an important role in increasing public understanding and participation.